42+4x=62-1x

Simple and best practice solution for 42+4x=62-1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42+4x=62-1x equation:


Simplifying
42 + 4x = 62 + -1x

Solving
42 + 4x = 62 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
42 + 4x + x = 62 + -1x + x

Combine like terms: 4x + x = 5x
42 + 5x = 62 + -1x + x

Combine like terms: -1x + x = 0
42 + 5x = 62 + 0
42 + 5x = 62

Add '-42' to each side of the equation.
42 + -42 + 5x = 62 + -42

Combine like terms: 42 + -42 = 0
0 + 5x = 62 + -42
5x = 62 + -42

Combine like terms: 62 + -42 = 20
5x = 20

Divide each side by '5'.
x = 4

Simplifying
x = 4

See similar equations:

| 4x+7y-7z=-10 | | -4-7x=66 | | OnehalfX+16=39 | | x^2+4x-5y^2+20y-20=0 | | -17x-14=-150 | | 137=28x*428+37 | | (7-3i)(-2-5i)=0 | | 9y+3-y=12y | | 9r+1-7r+1=-15 | | -28x+32x=-30 | | 0.12-0.02(x+3)=-0.03(3-x) | | .33w=2.5 | | -3.6=2f | | 10(t-3)+4t=7(2t+2)-9 | | 19(4.5-.25x)+x=13 | | -32=-4(v+9) | | (3a+4)(9a+7)= | | .4(60+16s)=15+4s | | -2a-9=10t+14 | | 3x^2-72x=-432 | | -8x-8(-4x+13)=16 | | 2(u+4)-6u= | | 20-18.67= | | 16w=2.5 | | 7=3(n+2) | | (3+6j)(5-j)= | | -30x+-32x=-15 | | -9y=6 | | .2x+.7=1.9 | | 2x-6=1.5+1 | | 3s^2=19s+14factor | | 112-14x=392 |

Equations solver categories